2011
DOI: 10.1002/rcs.385
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted laparoscopic management of cardia carcinoma according to Siewert recommendations

Abstract: Robot-assisted laparoscopic radical surgery of the oesophago-gastric junction is feasible and safe. Longer follow-up time and randomized studies are needed to evaluate the long-term outcome and advantages for the patient of this new technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Furthermore, laparoscopic liver surgery is still restricted to tertiary centres with experience in both hepatic and laparoscopic surgery. Conversely, robot‐assisted surgery has been shown to be feasible even for surgeons without extensive experience in laparoscopic surgery and to facilitate procedures considered demanding with a traditional laparoscopic approach, such as radical prostatectomy, gastric surgery and low anterior rectal resection . Whether this facilitation could also be extended to liver surgery is still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, laparoscopic liver surgery is still restricted to tertiary centres with experience in both hepatic and laparoscopic surgery. Conversely, robot‐assisted surgery has been shown to be feasible even for surgeons without extensive experience in laparoscopic surgery and to facilitate procedures considered demanding with a traditional laparoscopic approach, such as radical prostatectomy, gastric surgery and low anterior rectal resection . Whether this facilitation could also be extended to liver surgery is still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 5 years the number of laparoscopic complex liver resections has increased and even major hepatectomies and segmentectomies of the postero‐superior (P–S) segments have been successfully performed . Recently robotics has been introduced in general surgery, with the aim of overcoming some of the limitations of traditional laparoscopy, providing greater manoeuvrability with a set of articulated instruments and a three‐dimensional (3D) view . The first application of robotics in liver surgery dates back to 2003 (in Italy), whereas the first series of left lateral sectionectomy dates back to 2008 (in South Korea) .…”
Section: Introductionmentioning
confidence: 99%
“…Various RAL gastrectomy series and their comparative results are summarized in Table 1 (14,(25)(26)(27)(28)(29)(30)(31). It should be borne in mind that in most of the articles reviewed, the robotic-assisted operations were performed by highly experienced surgeons, and the outcomes could have been altered with different surgical teams possessing variable levels of experience.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, reports of LTH resection for AEG with esophagojejunal anastomosis are lacking, probably due to the difficulties associated with anastomotic techniques. Only Patriti et al 19 has reported the preliminary outcomes of robot-assisted LTH resection in 17 patients with cardia cancer, including 3 cases of AEG type II.…”
Section: Discussionmentioning
confidence: 98%